High level of psychological stress in COVID-19 recovered individuals: role of copeptin as a potential biomarker - Nonglait, Phibakordor Lyngdoh; Madhu, Sri Venkata; Raizada, Nishant; Aggarwal, Amitesh; Ahmed, Rafat; Aslam, Mohammad (Frontiers in Psychology, 2023)
Background Study aimed to assess stress in COVID-19 recovered individuals using a validated questionnaire PSS-10 score and stress biomarkers – salivary cortisol and serum copeptin. Methods A total of 83 subjects of which 54 subjects (66.3%) who were hospitalized were recruited 8–20 weeks following recovery from COVID-19. Stress was assessed by PSS-10 stress-scale after a mean duration of 14.5 weeks after recovery. Sixty-eight subjects (81.9%) had new or persistent symptoms after recovery. Subjects were divided into two groups on the basis of PSS score; mild stress (PSS:0–13) and moderate to severe stress (PSS:>14) and levels of biomarkers (serum copeptin, DHEAS and salivary cortisol) were compared in the two groups. Results Forty-four subjects (53%) had moderate to severe stress and 39 subjects (47%) had mild stress. Subjects with post COVID symptoms had significantly higher stress levels as compared to subjects who were asymptomatic [15 vs. 9; p = 0.003]. Serum copeptin levels were significantly higher among subjects with moderate to severe stress as compared to those with mild stress [0.41 vs. 0.67 ng/mL; p = 0.031]. Subjects with moderate to severe stress had higher median salivary cortisol compared to subjects with mild stress [1.03 vs. 1.44 nmol/L; p = 0.448]. Conclusion Our study demonstrated moderate to severe stress in over half and some level of stress in nearly all COVID recovered individuals even after 3 months. Serum copeptin was found to be a useful biomarker to objectively measure stress in these subjects.